1991
DOI: 10.1111/j.1151-2916.1991.tb06859.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Changes in the Structure of Hardened C3S Cement Pastes due to Carbonation

Abstract: The structures of partially carbonated hardened C3S cement pastes have been investigated by a combination of 29Si magic angle spinning nuclear magnetic resonance spectroscopy and analytical transmission electron microscopy, supported by X-ray diffraction and thermogravimetric analysis. Progressive changes in structure are reported for thin slices for a paste carbonated in pure COz for times from 1 to 16 h, and the results are compared with those for a paste carbonated for 2 months in air. C-S-H gel of reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(127 citation statements)
references
References 6 publications
12
112
0
3
Order By: Relevance
“…• C is consistent with data from the literature in the case of accelerated conditions of carbonation [12,8,5,68,46,69,4,47]. Sauman [13] attributes the first peak (750…”
Section: Tga-dtg-ms and Xrd Characterizationsupporting
confidence: 80%
See 1 more Smart Citation
“…• C is consistent with data from the literature in the case of accelerated conditions of carbonation [12,8,5,68,46,69,4,47]. Sauman [13] attributes the first peak (750…”
Section: Tga-dtg-ms and Xrd Characterizationsupporting
confidence: 80%
“…This phenomenon has already been highlighted in the literature [45,5,68]. It would be related to a reduction of accessibility of CH cristals due to the formation of a coating of CC which would hinder CH dissolution.…”
Section: Tga-dtg-ms and Xrd Characterizationmentioning
confidence: 86%
“…In the literature, it has been widely reported that carbonation products of hydrated cementitious minerals are calcium carbonate, modified silica gel, and alumina gel (10,42,43). This allows us to suggest that both anhydrous and hydrated calcium silicate/aluminate minerals found naturally or as constituents of wastes (i.e., ash, slag, and construction waste) represent suitable raw materials for sorbent production by accelerated carbonation.…”
Section: Casm Characterization (A) X-ray Analysis Of Casm (mentioning
confidence: 87%
“…The carbonation of C-S-H gel forms acid-stable silica gel (Q 3 and Q 4 ). According to recent studies, 14,15) a higher degree of carbonation of the hardened OPC leads to produce a higher crystallinity of the calcite and greater polymerization of the silica gel. Figure 5 presents X-ray diffraction patterns of the waste cements carbonated at various carbonation times.…”
Section: Resultsmentioning
confidence: 99%